Responsible Land Governance and Project Management Competences for Sustainable Social Development. The Chilean-Mapuche Conflict - BugueÃ±o, Felipe; RÃos, Ignacio De Los; CastaÃ±eda, Rodrigo (International Journal of Economics and Financial Issues, 2018)
Responsible land governance can contribute to achieve social development, decreasing poverty and famine and reach an inclusive economic development. Agroforestry system comprises a wide range of stakeholders and diverse social, political, economic and natural environments. The conflict between some mapuche communities and the Chilean State has been maintained since the XIX century due to how the public and private projects have been managed and to the type of land tenure and governance, cultural recognition, identity and ancestral rights. Currently, the conflict is a matter of political, social and cultural contingency. Using the “Working with people” planning model, this investigation analyse the current governance in the zone and prove that with the consideration of IPMA competences by the stakeholders it is possible to promote a resolution, creating the instances for a responsible land governance. Further it is proposed that the multilateral organizations have to deepen the work with different organizations. Keywords: IPMA Competences; Working with people; Sustainable rural development. JEL Classification: Q15